Analisis Dampak Pernikahan Dini terhadap Keharmonisan Keluarga Perspektif Hukum Islam di Era Digital - Nazril Muntazar (Posita: Jurnal Hukum Keluarga Islam, 2026)
The phenomenon of early marriage in Indonesia remains a significant social issue with various implications for individual and family life, particularly in the digital era characterized by massive penetration of information technology and social media. This study aims to analyze the impact of early marriage on family harmony from the perspective of Islamic law in the digital era. The research method employed is library research with a qualitative approach, where data were collected from primary sources including Islamic jurisprudence books, legislation, and MUI fatwas, as well as secondary sources comprising relevant scientific journal articles and books. Data analysis was conducted using content analysis and thematic analysis methods. The results indicate that early marriage negatively affects family harmony through decreased communication quality, limited economic capacity, and vulnerability to negative digital media influences. The Islamic law perspective emphasizes that the marriage goal of realizing a sakinah, mawaddah, wa rahmah family is difficult to achieve when couples lack adequate physical, mental, and financial readiness. The digital era exacerbates these challenges through exposure to negative content, online social pressure, and shifting communication patterns. The conclusion confirms that early marriage significantly hinders the realization of family harmony within the Islamic legal framework, thus requiring strengthened regulation, comprehensive premarital education, and digital literacy for young couples.